2020
DOI: 10.18632/oncotarget.27707
|View full text |Cite
|
Sign up to set email alerts
|

SNPs in the interleukin-12 signaling pathway are associated with breast cancer risk in Puerto Rican women

Abstract: Interleukin-12 (IL-12) is a proinflammatory cytokine that links innate and adaptive immune responses against tumor cells. Single Nucleotide Polymorphisms (SNPs) in IL-12 genes have been associated with cancer risk. However, limited studies have assessed the role of IL-12 in breast cancer (BC) risk comprehensively, and these were done in European and Asian populations. Here, we evaluated the association of the IL-12 signaling pathway and BC risk in Puerto Rican women. A genetic association study was completed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
0
8
1
Order By: Relevance
“…Consistent with its important role in regulating the immune response, IL-12 has been confirmed to be tightly associated with immunerelated diseases (36). Epidemiological studies have found that IL-12 polymorphisms are closely related to cancers (37). Due to its ability to activate cytotoxic cells from the immune response, IL-12 is regarded as a potential antitumor drug (38).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with its important role in regulating the immune response, IL-12 has been confirmed to be tightly associated with immunerelated diseases (36). Epidemiological studies have found that IL-12 polymorphisms are closely related to cancers (37). Due to its ability to activate cytotoxic cells from the immune response, IL-12 is regarded as a potential antitumor drug (38).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that these mutations did not present a risk factor for sporadic CRC and that they would rather be associated with a potential protective effect. We observed that genetic studies increasingly show that mutations have a potential protective role in certain multifactorial diseases (Yamamoto-Furusho et al, 2011), in particular cancerous pathologies (Tong et al, 2012;Núñez-Marrero 2020). Globally, association studies of these SNPs with sporadic CRC are rare.…”
Section: Discussionmentioning
confidence: 99%
“…This deficit abolishes both IL-12 and IL-23 signaling pathways (Núñez-Marrero 2020). On the other hand, still concerning breast cancer, certain variations (in particular the rs438421 SNP) would be protective by improving the activity of the IL-12R receptor, thus promoting the production of IFN-γ especially in cytotoxic T cells (van de Vosse et al, 2013;Núñez-Marrero 2020). Furthermore, beyond the mutations favorable to the development of the disease or those which would be protective of it, rare variations and other common ones with an unknown functional effect have been reported for IL-12RB1 (van de Vosse et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To deeply discover new markers related to the etiology, progression and prognosis of lymphoma, we used the Agena Massarray technology platform to detect 25 candidate SNPs of 21 genes (TNFA, IFNG, IFNL3, IL2, IL4, IL6R, IL9, IL10, IL12A, IL22, TGFB1, TBX21/TBET, STAT1, STAT3, STAT5B, STAT6, GATA3, NFKBIA, ITGAM, PTPN22, PARP1) in 245 lymphoma patients and 213 healthy controls 8,10,16–57 . All the 25 candidate SNPs were based on previous research studies about immune‐related genetic polymorphisms on the susceptibility, prognosis, progression and stage of many cancers.…”
Section: Introductionmentioning
confidence: 99%